Space@Sea the Floating Solution - Flikkema, Maarten; Waals, Olaf (Frontiers in Marine Science, 2019)
This paper describes the Horizon 2020 project Space@Sea [1] which started in November 2017. This project aims to provide a concept of affordable and flexible floating islands. With increasing population and rising sea level there is a scarcity for space on land for the people to live, grow food and harvest renewable energy. Moreover, a large number of people live in areas that are exposed to the risk of flooding in case of sea level rise. These trends call for a solution at sea that creates a new perspective. Previous projects on floating habitation such as the TROPOS project [2] have delivered artist impressions. Technical solutions are yet to be provided. In the Space@Sea project a conceptual study is done to develop a standardised floating solution for offshore space. Four applications focussing on energy hub, living, aquaculture and maritime transport will be demonstrated. For two locations a business case of a combination of these applications will be examined. The present paper discusses the Space@Sea project background and approach of the collaborative research. First results regarding the basic design and societal acceptance are discussed at a high level. Throughout the Space@Sea project results will be published on Frontiers in Marine Science.